Non-Verbal Communication by Autistic Children - Irga Safira; Rahmadsyah Rangkuti; Ely Hayati Nasution (English Teaching and Linguistics Journal (ETLiJ), 2021)
This thesis entitled ‘Non-Verbal Communication by Autistic Children’ was conducted with the aim to find out the components of kinesics as a part of nonverbal communication expressed by autistic children when interacting with their teachers at SLB ABC Taman Pendidikan Islam. Beside that this study also intended to know the meanings of those kinesics components expressed by autistic children when interacting with their teachers. This research used a descriptive qualitative approach by applying kinesics theory by Ray Birdwhistell. The data collection techniques were conducted by using non-participant observation techniques and documentation. The documents used to support this study were in the form of photographs and video recorder that showed the communication done by the autistic children with their teachers during the learning process in the class. The results showed that although autistic children cannot interact clearly through verbal communication, they can express their desires through non verbal communication. They can communicate by expressing it through facial expressions, eye contact, body movement, posture and touch. The meaning of the non-verbal communication expressed by each autistic child has a different meaning. This study also intended to give worthy contribution to all people who want to understand the non-verbal communication of autistic children.